PENGGUNAAN MODEL PEMBELAJARAN COOPERATIVE TIPE NUMBER HEAD TOGETHER UNTUK MENINGKATKAN HASIL BELAJAR BIOLOGI : (Improving Students’ Learning Biology Outcomes Using a Numbered Head Together Type of Cooperative Learning Model) - Nuraeni, Nuraeni (Uniqbu Journal of Exact Sciences, 2023)
The aim of this study is to see how the Number Head Together Cooperative Learning Model may be used to improve biology learning outcomes in Class XI Mathematics and Natural Sciences at Madrasah Aliyah Negeri Masamba. While the research method employed in this study is classroom-based action research, the research subjects are MAN Masamba Class XI 1 MIPA students. There are 25 students in all, including 7 boys and 18 girls. Planning, action, observation and assessment, and reflection are all part of the study implementation procedure. Furthermore, this study’s working technique is divided into TWO cycles. Cycle I have three meetings, and Cycle II has four meetings. Data gathering methods include the last test of each cycle and observation. The descriptive analysis yielded the following results: (1) the average value of student learning outcomes in the first cycle is 73.40, with a percentage of completeness as high as 68.0%; and (2) the average value of student learning outcomes in the second cycle is 76.00, with a percentage of completeness as high as 84.0%. (2) The Number Head Together (NHT) cooperative strategy can improve the biology learning results of students in class XI MIPA 1 MAN Masamba.